5a+7a-6b-3a=

Simple and best practice solution for 5a+7a-6b-3a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5a+7a-6b-3a= equation:


Simplifying
5a + 7a + -6b + -3a = 0

Reorder the terms:
5a + 7a + -3a + -6b = 0

Combine like terms: 5a + 7a = 12a
12a + -3a + -6b = 0

Combine like terms: 12a + -3a = 9a
9a + -6b = 0

Solving
9a + -6b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '6b' to each side of the equation.
9a + -6b + 6b = 0 + 6b

Combine like terms: -6b + 6b = 0
9a + 0 = 0 + 6b
9a = 0 + 6b
Remove the zero:
9a = 6b

Divide each side by '9'.
a = 0.6666666667b

Simplifying
a = 0.6666666667b

See similar equations:

| 2(2n-3)=2n-2(n-1) | | m=4+m | | -5(-2x+3)= | | 7x-3y+9x-2y= | | Dx+9y=27 | | 5/8(x-7)=10 | | logv[12](x)+logv[12](11x-1)=1 | | 12x+5y=8400 | | 12x=6x+20-8 | | 5p+7s+4p-3s= | | 4x-32=9x+17 | | 15m^2-5m^2=30m+11m | | 7x+4y+2x-6y= | | 3x+7=5x-q | | 5x+12y=8400 | | 27=9s | | 10x-5=8x+15 | | (2x-3)/(5-3x)0 | | =(x+y-1)+(x+y+1)-(x+y-z) | | 4b-9b= | | 3x-20=x+8 | | 9+35r+25r=35r+34r | | x=3x^2+2x+6 | | F+2f+4f= | | x^2+y^2-10x+9y+1=0 | | 81/:5/6 | | 5p+3p+4p= | | x^2y^2-10x+9y+1=0 | | -16-(-38)=x/5 | | log(3)+log(2)= | | y[(x^3)(y^3)+(2x^2)-(y)]dx+[(x^4)(y^3)-(2x^3)]dy=0 | | k=3r-8 |

Equations solver categories